SURGICAL SITE INFECTION: ARE SURVEILLANCE AND RISK PREVENTION MEASURES INSTITUTIONALLY APPLIED? - Larissa Bianca Leite Batista; Sabrina Bianca Azevedo Silva; Dulce Aparecida Martins; Maristela Oliveira Lara; Thabata Coaglio Lucas (Universidade Federal do Paraná, 2019)
Objective: this study aimed to evaluate measures of surveillance and prevention of surgical site infections in a philanthropic institution in the interior of Minas Gerais.Method: quasi-experimental study with pre-intervention, intervention and post-intervention period. We used Pearson's Chi-Square test when the expected value was >5 and Fisher's exact test for the expected value <5. The Bonferroni correction was applied for multiple comparisons (p<0.01). Results: the trichotomy was performed with a slide for removal by 66% of professionals. The patient's temperature was significant (p=0.03) when associated with the professional category. 84% of the surgeons did antimicrobial prophylaxis prior to surgical incision. In the post-intervention phase, there was a reduction of 84.6% of the professionals who prepared the skin before the surgical incision. Conclusion: the present study generated quality indicators for the surgical center and, in the absence of follow-up protocols, underestimated adverse events resulting from surgery.